GAMBARAN PENERAPAN NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA SUB SEKTOR PERUSAHAAN INVESTASI PADA TAHUN 2011-2016 - Nuurohman, Fajar; Tarmedi, Eded; Mayasari, Mayasari (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Objectives - The purpose of this study is to find out how the picture of the application of net profit margin and earnings per share to stock prices in the sub-sector of investment companies in 2011-2016design / methodology / approach - The method used in this research is descriptive and verifikatif method. The data used are secondary data from each company sub sector of investment company in year 2011-2016 with analysis technique using multiple regression. Sampling in this research use purposive sampling.Findings - The results of this study indicate that, the application of net profit margin effect on stock prices. earnings per share effect on stock prices. The results showed that the application of net profit margin and earnings per share a positive influence on stock prices.Originality - Differences of research with previous research is on the object, population and sample research, the study period, measuring instruments and research results, as well as sources of foreign theories and journals and foreign books and research results